Beyond identity: Membership norms and regional organization. (March 2017) - Thomas, Daniel C.
What is a region and how can we best understand a state's eligibility for membership in a regional political community? Scholars have sought to answer these questions in terms of geographic proximity and social-psychological identity, but neither concept can accommodate the contestation and change that characterize the social construction of regions. Instead, this article argues that the limits of regions are defined within regional organizations by member states' governments plus supranational actors deliberating over a common definition of the characteristics that members and potential members are expected to share. The concept of membership norms thus offers powerful insights into how regional communities define who is eligible for membership, how these definitions change over time and the incentives they create for those seeking to promote or block an applicant state. The evolution of the European Union's membership norms since the 1950s illustrates this argument.